PENGARUH PEMBERIAN PUPUK KANDANG AYAM DAN PUPUK NPK 17:17:17 TERHADAP PERTUMBUHAN BIBIT TANAMAN PORANG (Amorphophallus oncophyllus) - Manik, Surhani; Rosmaiti, Rosmaiti; Adnan, Adnan (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
This study aims to determine the effect of giving chicken manure and NPK 17:17:17 fertilizer to the growth of Porang seedlings, as well as the interaction between the two. This study used a Randomized Block Design (RAK) with 2 factorials, namely, treatment of chicken manure (K) doses with 3 levels, namely: K1 = 20 gr/polybag, K2 = 40 gr/polybag and K3 = 60 gr/polybag, and treatment dose of NPK 17:17:17 (N) fertilizer with 3 levels, namely: N1 = 5 gr/polybag, N2 = 6 gr/polybag and N3 = 7 gr/polybag. The parameters observed in this study were: plant height (cm), stem diameter (cm), leaf width (cm) and number of leaves (strands). The results showed that the application of chicken manure had a significant effect on the leaf width parameter (cm). The best results were obtained in the K2 treatment (40 g/polybag). The application of NPK 17:17:17 fertilizer had a very significant effect on plant height (cm), stem diameter (cm) and number of leaves (strands). The best results were obtained in the N1 treatment (5 g/polybag). There is no interaction between chicken manure and NPK fertilizer 17:17:17.